2008
DOI: 10.1016/j.bmcl.2008.06.086
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of inhibitor effects on enzyme activity and thermal stability for the integral membrane protein fatty acid amide hydrolase

Abstract: The melting curves of fatty acid amide hydrolase (FAAH) in the presence of 29 reversible inhibitors were measured using a thiol-reactive fluorophore. The thermal stability (T m ) of the FAAH/inhibitor complex varied significantly depending on the chemical characteristics of the inhibitors, notably variations in the head group. Two separate distributions were observed when T m was plotted againt K i . The majority of the inhibitors showed a positive correlation between binding affinity and T m , however inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…The ligand binds selectively to the native (functional) form and alters the structure of the target protein (or selects for a stable conformer) and thereby protects the protein from thermally-induced denaturation. Not surprisingly, these stabilizing ligands tend to be inhibitors, rather than activators (60). …”
Section: Discussionmentioning
confidence: 99%
“…The ligand binds selectively to the native (functional) form and alters the structure of the target protein (or selects for a stable conformer) and thereby protects the protein from thermally-induced denaturation. Not surprisingly, these stabilizing ligands tend to be inhibitors, rather than activators (60). …”
Section: Discussionmentioning
confidence: 99%
“…In this study and in addition to demonstrating that the observed increased thermal stability qualitatively parallels an inhibitor’s potency, the 2-pyridyl-6-carboxylic acid derivatives exhibited a uniquely strong stabilizing effect among the various series examined, suggesting they constitute an especially interesting series to examine in greater detail. 34 …”
Section: Reversible Faah Inhibitorsmentioning
confidence: 99%
“…however, several communications describe combined analyses of potency versus thermal stability. 12,14,15 Very interestingly, in their study on the fatty acid amide hydrolase, slaymaker et al 15 were able to identify two different compound populations once they plotted a graph lnK i versus t m . unfortunately, no thermodynamic measurements were realized with these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…the binding of a ligand to a protein leads to the formation of a complex protein-ligand that usually exhibits a higher melting temperature, t m b , than the free protein. experiments have shown a good correlation between ligand potency measured in biochemical assays and shift in melting temperatures (Δt m = t m b -t m ) estimated in ftsa, [12][13][14][15] and ftsa is already routinely used to triage hits identified from high-throughput screening (hts) campaigns. moreover, Δt m s obtained from ftsa are directly connected to the thermodynamic parameters of the ligand-protein interaction, 7,16,17 providing a link to the thermodynamic signatures of the compounds.…”
mentioning
confidence: 99%